2017
DOI: 10.1371/journal.pone.0171715
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the structural and functional diversity of zooplankton over vertical and horizontal environmental gradients en route to the Arctic Ocean through the Fram Strait

Abstract: A multi-scale approach was used to evaluate which spatial gradient of environmental variability is the most important in structuring zooplankton diversity in the West Spitsbergen Current (WSC). The WSC is the main conveyor of warm and biologically rich Atlantic water to the Arctic Ocean through the Fram Strait. The data set included 85 stratified vertical zooplankton samples (obtained from depths up to 1000 metres) covering two latitudinal sections (76°30’N and 79°N) located across the multi-path WSC system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 100 publications
7
27
0
Order By: Relevance
“…Such similarity in the Calanus age structure observed in Rijpfjorden and Hornsund indicates a coincident timing of reproductive events and its synchrony with ice algae bloom in April and phytoplankton bloom in July [96]. In addition, the presence of early copepodite stages in all the studied periods (this study) might suggest continuous reproduction, or at least, the presence of more than one generation of Calanus, which is likely in high latitudes according to several new studies [20,65,97]. In Kongsfjorden, the trend of a gradual population development was observed in this work only in 2015.…”
Section: Discussionsupporting
confidence: 78%
“…Such similarity in the Calanus age structure observed in Rijpfjorden and Hornsund indicates a coincident timing of reproductive events and its synchrony with ice algae bloom in April and phytoplankton bloom in July [96]. In addition, the presence of early copepodite stages in all the studied periods (this study) might suggest continuous reproduction, or at least, the presence of more than one generation of Calanus, which is likely in high latitudes according to several new studies [20,65,97]. In Kongsfjorden, the trend of a gradual population development was observed in this work only in 2015.…”
Section: Discussionsupporting
confidence: 78%
“…Over the last decades this AW inflow has become warmer (Beszczynska-Möller et al, 2012), and it has been identified as the main mediator of climate change in the Arctic marine environment (Spielhagen et al, 2011;Polyakov et al, 2012;Onarheim et al, 2014). In addition to heat, the AW current transports phytoplankton (Hegseth and Sundfjord, 2008;Metfies et al, 2016) and zooplankton of Atlantic origin, and with different functional roles (Kosobokova and Hirche, 2009;Kraft et al, 2013;Gluchowska et al, 2017b). Changes in ecosystem structure at lower latitudes are thus advected into the Arctic Basin and affect productivity and carbon cycling (Hunt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For Arctic standards, this data set is unique due to its spatial and temporal coverage. While these data have been used to analyze how environmental variables shape the distribution of key Calanus species , zooplankton community structure (Weydmann et al, 2014;Gluchowska et al, 2017a), zooplankton structural and functional diversity (Gluchowska et al, 2017b), and population development of Calanus finmarchicus (Gluchowska et al, 2017a;Weydmann et al, 2018), the spatial and temporal variability in the zooplankton community has not yet been fully explored.…”
Section: Introductionmentioning
confidence: 99%